Spelling Impairments in Italian Dyslexic Children with and without a History of Early Language Delay. Are There Any Differences? - Angelelli, Paola; Marinelli, Chiara V.; Iaia, Marika; Putzolu, Anna; Gasperini, Filippo; Brizzolara, Daniela; Chilosi, Anna M. (Frontiers in Psychology, 2016)
Language delay is considered a frequent antecedent of literacy problems and both may be linked to phonological impairment. However, while several studies have examined the relationship between language delay and reading impairment, relatively few have focused on spelling. In this study, spelling performance of 28 children with developmental dyslexia (DD), 14 children with a history of language delay (LD) and 14 children without (NoLD) and 28 control participants were examined. Spelling was investigated by writing a dictation task that included orthographically regular stimuli (word and nonwords), as well as words with unpredictable transcription. Results indicated that all dyslexic participants underperformed compared to controls on both regular and unpredictable transcription stimuli, but LD performance was generally the worst. Moreover, spelling impairment assumed different characteristics in LD and NoLD children. LD children were more sensitive to acoustic-to-phonological variables, showing relevant failure especially on stimuli containing geminate consonants but also on polysyllabic stimuli and those containing non-continuant consonants. Error analysis confirmed these results, with LD children producing a higher rate of phonological errors respect to NoLD children and controls. Results were coherent with the hypothesis that among dyslexic children, those with previous language delay have more severe spelling deficit, suffering from defective orthographic lexical acquisition together with long-lasting phonological difficulties.